Analysis of Carotene in Biscuits made from Yellow Pumpkin Flour (Cucurbita moschata Durch) at Various Heating Temperatures - Yuldayani; Supriadi (Jurnal Akademika Kimia, 2023)
Yellow pumpkin (Cucurbita moschata Durch) is one of the food ingredients rich in dietary fibers, especially pectin, bioactive compounds, beta carotene, vitamin A, tocopherol, other vitamins including B6, K, C, thiamine, and riboflavin, as well as several types of minerals (K, P, Mg, Fe, and Se). This study aimed to determine the carotene retention of biscuits made from pumpkin flour (Cucurbita moschata Durch) at various heating temperatures. This study's stages included preparing pumpkin flour and biscuits, carotene content, and carotene retention analysis from various heating temperatures. Determination of carotene retention using a UV - Vis spectrophotometer. The results showed that the roasting temperature influenced carotene retention in the preparation of biscuits. Biscuits with retention of 86 % were found at a temperature of 190 oC. The lowest carotene retention of 79 % was found at a roasting temperature of 210 oC.